South Africa within SADC : hegemon or partner? - Molefi, Tebogo Shadrack (Rhodes University, Faculty of Humanities, Department of Political Studies, 2003)
This study attempts to make a contribution to the debate on the role of South Africa within Southern African Development Community. An attempt is made to analyse this role within the context of regional integration debate. This role has been conceptualised within the dichotomies of hegemon versus partner. The study argues that South Africa is a hegemon in the region of SADC, and that given its overarching economic dominance and it has the potential of establishing its hegemony in the region. It maintains that there are several factors, which could facilitate South Africa's hegemonic dominance such as in military, technology and manufacturing sector. It concludes by arguing that given the changing geopolitical factors both within the region and the globe impedes South Africa from firmly expressing this hegemonic dominance. Furthermore, South Africa's pioneering role in the struggle to change the status quo globally in favour of the Southern states is another crucial factor, which imposes limitations on its hegemonic intentions regionally.
Keywords: Southern African Development Community; Political stability -- Africa, Southern; South Africa -- Economic conditions; South Africa -- Foreign relations -- Africa; South Africa -- Economic policy